2005
DOI: 10.1021/jm050683z
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Molecular Modeling of a Novel Amide-Linked Cyclic GnRH Analogue Cyclo(4−9)[Lys4,d-Trp6,Glu9]GnRH:  Stimulation of Gonadotropin Gene Expression

Abstract: This report describes the rational design, synthesis, and pharmacological properties of an amide-linked cyclic analogue of gonadotropin-releasing hormone (GnRH) namely Cyclo(4-9)[Lys(4),d-Trp(6),Glu(9)]GnRH. The conformationally restricted analogue is characterized by reduced flexibility of the peptide strand due to the introduction of a beta-turn mimetic through 4,9 residue amide cyclization. The cyclic analogue was found to stimulate gonadotropin gene expression in the goldfish pituitary with similar potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
10
0
5
Order By: Relevance
“…Intramolecular cyclization has been demonstrated to improve biological properties of bioactive peptides [28][29][30][31][32][33][34][35][36][37][38], in many cases allowing one to improve selectivity for a given receptor and/or metabolic stability [39][40][41]. Cyclic peptides can be divided into homodetic and heterodetic, the first being obtained by formation of an intramolecular peptide (amide) bond, whereas heterodetic refers to all cyclic peptides where the intramolecular bond newly formed is other than an amide (e.g., lactone, ether, thioether and, most commonly, disulphide bridges).…”
Section: Peptide Carriers A) Peptide Cyclization and Prodrug Designmentioning
confidence: 99%
“…Intramolecular cyclization has been demonstrated to improve biological properties of bioactive peptides [28][29][30][31][32][33][34][35][36][37][38], in many cases allowing one to improve selectivity for a given receptor and/or metabolic stability [39][40][41]. Cyclic peptides can be divided into homodetic and heterodetic, the first being obtained by formation of an intramolecular peptide (amide) bond, whereas heterodetic refers to all cyclic peptides where the intramolecular bond newly formed is other than an amide (e.g., lactone, ether, thioether and, most commonly, disulphide bridges).…”
Section: Peptide Carriers A) Peptide Cyclization and Prodrug Designmentioning
confidence: 99%
“…Thus, initially the synthesis of the analogue was performed by the Fmoc/tBu methodology, utilizing the 2-chlorotrityl chloride (CLTR-Cl) resin [34][35][36][37][38][39]. The side chains of the amino acids were protected as follows: trityl group (Trt) for His, 2,2,4,6,7-pentamethyldihydrobenzofurane group (Pbf) for Arg and tert-butyl group (tBu) for Ser and Tyr.…”
Section: Synthesismentioning
confidence: 99%
“…Recent directions of these modified peptides in applied research have resulted in the design and synthesis of cyclic peptide analogues of immunodominant epitopes of myelin basic protein (MBP) and myelin oligodendrocyte glycoprotein (MOG) providing novel therapies for Experimental Autoimmune Encephalomyelitis (EAE, the best well‐studied animal model of Multiple Sclerosis, MS) (Figure ). Also, gonadotropin‐releasing hormone (GnRH) cyclic peptides have been designed and synthesized for their ability to act as agonists or antagonists. Moreover, grafting techniques are being applied to cyclotides, in order to attach biologically active fragments on their loops, therefore enhancing bioavalability and stability.…”
Section: Introductionmentioning
confidence: 99%
“…NMR studies on the endogenous 10‐residue hormone, GnRH and its analogues have identified a bend around the central amino acid at position 6. 50e,59 Further mutational studies, on the potent peptide leuprolide, which is used in the clinical setting, resulted in analogues with inhibition of cell proliferation . This information was used to design a series of cyclic peptides with non‐natural amino acids, resulting in a potent analogue, cyclo(1‐10)GnRH[Pro 1 , D Leu 6 , BABA 10 ], which showed enhanced proteolytic stability and improved pharmacokinetic properties…”
Section: Introductionmentioning
confidence: 99%